Conversion of Sago (Metroxylon sagu) Pith Waste to Fermentable Sugars via a Facile Depolymerization Process - Pang, Suh Cem; Lee, Ken Voon; Chin, Suk Fun (Humana Press Inc., 2018)
The conversion of starchy sago (Metroxylon sagu) pith waste (SPW), a lignocellulosic biomass waste, to fermentable sugars under mild conditions had been successfully demonstrated. The optimum depolymerization of SPW was achieved at 2 wt% sample loading which was catalyzed by 100 mM of oxalic acid in the presence of 25 wt% NaCl solution at 110 °C for 3 h. Up to 97% SPW sample was being converted into fermentable sugars with limited formation of by-products after two sequential depolymerization cycles. Both reaction temperature and concentration of oxalic acid were crucial parameters for the depolymerization of SPW which exhibited a high selectivity for the production of glucose over other reducing sugars. © 2017, Springer Science+Business Media, LLC.